Performance of asphalt mix with glass and glass-lime composite fillers - Choudhary J.; Kumar B.; Gupta A. (My University, 2025)
This study explored the potential of glass powder and glass—hydrated lime composite as mineral filler in asphalt mixes. For comparison, control mixes prepared with stone dust were taken for consideration. Physical and chemical characterization of filler materials is done as per relevant test standards. Marshall test procedure that has been recommended in Indian paving specification was used for mix design and evaluation. Other performance characteristics such as Marshall Quotients, indirect tensile strengths, retained Marshall stability values and Cantabro tests was evaluated. All three materials in consideration satisfied the criteria for mineral filler specified in Indian specifications. Glass powder was found to deliver superior performance in terms of Marshall Stability, Marshall Quotient, Indirect tensile strength and optimum binder content when compared with stone dust mixes. However, it became frail in presence of moisture due to predominance of Silica in its composition. Glass-lime composite is proven to be best filler amongst three, since not only it delivered best performance in terms of strengths and optimum binder content, but also it displayed moisture resistance almost similar to stone dust. © 2018 Taylor & Francis Group, London.